Upstroke Time Is a Useful Vascular Marker for Detecting Patients With Coronary Artery Disease Among Subjects With Normal Ankle‐Brachial Index - Maruhashi, Tatsuya; Kajikawa, Masato; Kishimoto, Shinji; Hashimoto, Haruki; Takaeko, Yuji; Yamaji, Takayuki; Harada, Takahiro; Hashimoto, Yu; Han, Yiming; Aibara, Yoshiki; Yusoff, Farina Muhamad; Hidaka, Takayuki; et al. (Journal of the American Heart Association, 2020)
Background Upstroke time is the transit time from the nadir to peak of the waveform of pulse volume recording. The purpose of this study was to determine whether upstroke time at the ankle is a useful vascular marker for detecting patients with advanced atherosclerosis in combination with ankle-brachial index (ABI). Methods and Results We measured upstroke time and ABI in 2313 subjects (mean age, 61.2±15.3 years). The prevalence of coronary artery disease (CAD) was significantly higher in patients with prolonged upstroke time (≥180 ms) than in subjects with normal upstroke time (<180 ms) (29.6% versus 11.8%; <0.001), with a significant association between prolonged upstroke time and an increased risk of CAD (odds ratio [OR], 1.61; 95% CI, 1.07-2.44; =0.02). In 1954 subjects with normal ABI (1.00 ≤ ABI ≤ 1.40), the prevalence of CAD was significantly higher in patients with prolonged upstroke time than in subjects with normal upstroke time (29.5% versus 10.6%; <0.001), with a significant association between prolonged upstroke time and CAD (OR, 2.33; 95% CI, 1.41-3.87; =0.001), whereas there was no significant association between upstroke time and CAD in subjects with low ABI (<1.00) (OR, 1.24; 95% CI, 0.72-2.16; =0.44). Conclusions Upstroke time may be a useful vascular marker for detecting patients with CAD, especially in subjects with normal ABI who are usually considered not to have advanced atherosclerosis by ABI measurement alone. More attention should be paid to upstroke time for detecting patients with advanced atherosclerosis. Registration URL: https://www.umin.ac.jp; Unique identifier: UMIN000039512.